Substantive defenses in the cases of the donor in the donation lawsuits - Al-Wazzan, Razan Yousef; Al-Mutawa, Asim Abdullah (Journal of Islamic Sciences, 2023)
This research aims to: collect and study the substantive defenses in the cases of the donor in the donation claims in the group of judicial rulings, in which I touched on the issues under these defenses, and mentioned the sayings of the four schools in them, and the evidence for each saying, and concluded each controversial issue by mentioning the most correct in it.I made the research composed of an introduction and a preamble with which the vocabulary of the title was defined, and it was divided into three sections: the first is entitled: “The argument that the inheritor was fully conscious at the time of the donation”, and the second is entitled: “The argument is that the donation was in the event of the validity of the inheritor and the completion of his legal capacity”, and the third Entitled: "The argument that the donation was in the disease of death."I concluded the research by mentioning the most important results in it, namely: that the donation is a permissible contract before taking possession, and it is necessary after it in the event that the donor is other than the father, and if the father is the contract is permissible for him even after taking possession, and that if the donor is terminally ill, the donation is valid only by one-third. Anything more is subject to the permission of the heirs.
Keywords: objective defenses; donation; donor conditions